EVALUATION OF FIELD JOB P RACTICE IMPLEMENTATION PROGRAM FOR THE STUDENT IS STATE VOCATIONAL HIGH SCHOOL 1 JAKARTA - Hawa Liberna (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2017)
Implementation of Hammond Model in Evaluation of Field Work Practice Program of State Vocational High School 1 Jakarta. The purpose of this study is to evaluate how the implementation of a program that has been selected in accordance with the purpose of information and implementation of a policy to take a decision. This research is taken one example of Hammond model implementation in Hammond model program evaluation one of program evaluation model that can help change learning to be better seen from 3 aspects that is learning, behavior, and institution. This Hammond program evaluation is a very helpful evaluation of the implementation of an existing school program for the better, in terms of these three aspects. In this research, the researcher evaluates the Field Work Practice program in STMN I Jakarta which has been running for more than 3 years and after the researcher conducted the research at State Vocational High School I many inputs from the researcher about the 3 aspects. And as an acceptable result is the implementation of Field Work Practices in Vocational Secondary School 1 will change its implementation in the first semester IX in the semester V. Because in the semester IX students sufficient knowledge to follow the implementation of Field Work Practices in the field to be better and competence.